Emerging and reemerging diseases in the environment of the Free Trade Agreement - Yuill, Thomas M. (Revista Colombiana de Ciencias Pecuarias, 2012)
A talk presented at the celebration of the 50th anniversary of the founding of the Faculty of Veterinary Medicine and of Animal Science (today "Faculty of Agrarian Sciences") of the Universidad de Antioquia, Medellín, Colombia 11 July, 2012.